Urolithin C, a gut metabolite of ellagic acid, induces apoptosis in PC12 cells through a mitochondria-mediated pathway. Issue 28 (20th March 2017) - Yin, Peipei; Zhang, Jianwei; Yan, Linlin; Yang, Lingguang; Sun, Liwei; Shi, Lingling; Ma, Chao; Liu, Yujun
Abstract : Urolithin C includes apoptosis in PC12 cells through a mitochondria-mediated pathway. Abstract : Urolithins (Uros), metabolites of ellagitannins (ET) and ellagic acid (EA) produced by gut microbiota, showed better bioavailability and extensive bioactivity, and were considered as the active compounds responsible for the health benefits exerted by ET-containing foodstuffs. Here, we chemically synthesized three Uros including Uros A, B, and C and compared their anti-proliferative activities with that of EA in PC12 cells. MTT assay showed that EA significantly promoted, while Uros significantly inhibited the proliferation of PC12 cells, among which UroC showed the strongest anti-proliferation. UroC treatment actively increased the lactate dehydrogenase (LDH) release and lipid peroxidation malondialdehyde (MDA), stimulated reactive oxygen species (ROS) formation and mitochondrial membrane depolarization, and caused calcium dyshomeostasis. Furthermore, flow cytometry analysis showed that UroC treatment induced apoptosis and S phase cell cycle arrest with increasing UroC concentrations. Consequently, UroC also induced imbalance in the Bcl-2/Bax ratio, which triggered the caspase cascade, thereby shifting the balance in favor of apoptosis, as evidenced by western blotting and real-time PCR. These observations indicated that UroC possessed significantly different anti-proliferation activities from EA, and actively induced cell apoptosis through a mitochondria-mediated pathway.